Unexpected waiting corrupts - Linda Dezsîo; Gergely Hajdu; Yossef Tobol (EcoAustria - Institute for Economic Research, 2024)
The experience of waiting is ubiquitous in all areas of life, and sometimes a waiting experi ence is followed by decisions where morality matters. We present the results of a lab-in-the-field study to analyze the effects of (un)expected waiting duration on moral behavior. Passengers who had just joined the check-in line at the Ben Gurion Airport guessed how long they would have to wait to check in. After checking in, they then completed the die-under-the-cup task, wherein they could lie without being caught to improve their financial outcomes. Specifically, passengers rolled a die privately and reported any number of dots, knowing that their earn ings increase linearly in the number reported. We found that both the wait duration and its unexpectedness adversely shape morality. For comparison, an expected 100-minute wait and an unexpected 25-minute wait resulted in the same average increase of one dot in the reported number. We propose that after a wait (especially if unexpected), people seek compensation. As we fail to find selections on observables, we argue that the setup provides variations that are comparable to random assignments, giving support to the effects estimated. These results underscore that managing expectations about waiting duration could play an important role in mitigating subsequent immoral behavior.
Keywords: C99; D91; 330; die-under-the-cup task; lying; expectations; compensation-seeking; waiting